Model-driven development of advanced user interfaces - Hussmann, Heinrich 1959-.; Meixner, Gerrit; Zuehlke, Detlef; SpringerLink (Online service). (Berlin Springer, 2011)
Model-Driven Development (MDD) has become an important paradigm in software development. It uses models as primary artifacts in the development process. This book provides an outstanding overview as well as deep insights into the area of model-driven development of user interfaces, which is an emerging topic in the intersection of Human-Computer-Interaction and Software-Engineering. The idea of this book is based on the very successful workshop series of ?Model-Driven Development of Advanced User Interfaces (MDDAUI). It has been written by the leading researchers and practitioners in the field of model-driven development of user interfaces and offer a variety of solutions and examples for ? Architectures and environments for the generation of user interfaces. User interface development for specific domains and purposes ? Model-driven development in the context of ambient intelligence ? Concepts supporting model-driven development of user interfaces.
1. Introduction -- 2. Architectures and Environments for the Generation of User Interfaces -- 2.1.1. A Design Space for User Interface Composition -- 2.1.2. Multi Front-End Engineering -- 2.1.3. Applying Meta-Modeling for the Definition of Model-Driven Development Methodology of Advanced User Interfaces -- 2.1.4. Using Storyboards to Integrate Models and Informal Design Knowledge -- 3. User Interface Development for Specific Domains and Purposes -- 3.1.1. Model-Driven Useware-Engineering -- 3.1.2. Automated GUI Generation with Optimization for Screens with Limited Resolution -- 3.1.3. Process-Centred Design of User Interfaces -- 3.1.4. A Formal Model-Based Approach for Designing Interruptions-Tolerant Advanced User Interfaces -- 4. Model-Driven Development in the Context of Ambient Intelligence -- 4.1.1. Runtime Adaptation of Model-Based User Interfaces for Smart Environments -- 4.1.2. MML: Model-Driven Development of Interactive Multimedia Applications -- 4.1.3. Taking Advantage of Model-Driven Engineering Fundaments for Mixed Interaction Design -- 5. Concepts Supporting Model-Driven Development of User Interfaces -- 5.1.1. T:XML: A Tool Supporting User Interface Model Transformation -- 5.1.2. Towards a Formal Model for Interaction Patterns -- 5.1.3. Task Models in the Context of User Interface Development -- 6. Summary -- 7. Index.
Electronic reproduction.
Keywords: Computer software -- Development; Software engineering; Model-driven software architecture; Electronic books